1996
DOI: 10.1063/1.117759
|View full text |Cite
|
Sign up to set email alerts
|

A kinetic mechanism for the formation of aligned (Bi,Pb)2Sr 2Ca2Cu3O10 in a powder-in-tube processed tape

Abstract: A two-step process is proposed for the formation of c-axis aligned (Bi,Pb)2Sr2Ca2Cu3O10+δ  [Bi(2:2:2:3)] platelets in a silver sheath. The process involves: (1) the formation of c-axis aligned (Bi,Pb)2Sr2CaCu2O8+δ  at early stage of heat treatment and (2) the subsequent intercalation of Ca–Cu–O layers to form Bi(2:2:2:3). This is based on the measurements of (1) the rocking curves for c-axis alignment and the two theta scans for the Bi(2:2:2:3) conversion ratio, both by a transmission x-ray technique, and (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 0 publications
5
37
1
Order By: Relevance
“…Indications of the presence of a liquid phase assisting the Bi,Pb(2223) phase formation were revealed by the presence of amorphous regions after quenching [8][9][10]. Accurate SEM observations allowed Grivel et al [11] to strongly support a nucleation-and-growth formation mechanism against a solid state intercalation mechanism [12]. The first direct proof of the presence of liquid occurring at high temperature as a consequence of the precursor decomposition was obtained by high temperature in-situ neutron powder diffraction (NPD) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indications of the presence of a liquid phase assisting the Bi,Pb(2223) phase formation were revealed by the presence of amorphous regions after quenching [8][9][10]. Accurate SEM observations allowed Grivel et al [11] to strongly support a nucleation-and-growth formation mechanism against a solid state intercalation mechanism [12]. The first direct proof of the presence of liquid occurring at high temperature as a consequence of the precursor decomposition was obtained by high temperature in-situ neutron powder diffraction (NPD) [13].…”
Section: Introductionmentioning
confidence: 99%
“…Our results do not provide direct evidence for either hypothesis, as 2223 formed with grea.ter texture than 2212. The explanation may be provided by Wang et al [13], who recently reported that 2212 is textured by a liquid phase during the 2223 reaction. However, it should be also noted that the increase in texture could be the result of constrained growth texturing [2], [3], [6], by which grains become textured during reaction to 2223 because they are geometrically constrained by the silver sheath or other aligned grains.…”
Section: Discussionmentioning
confidence: 98%
“…Alternatively, a 2212 dissolution /2223 crystallization mechanism is observed if a liquid phase develops during annealing [6]. Wang and coworkers [7] proposed a two-step process for the formation of 2223 phase in the (Bi,Pb)-Sr-Ca-Cu-O system: partial dissolution and re-growth of aligned 2212 followed by layerby-layer intercalation of CaCuO 2 planes into the 2212 aligned structure leading to the formation of 2223. In this work, it is demonstrated that the novel EAFLZ technique to grow superconducting fibres permits the development of large amounts of 2223 phase after thermal annealing, a scheme for the nucleation and growth mechanism being proposed.…”
Section: Introductionmentioning
confidence: 98%